Teriparatide (recombinant parathyroid hormone 1–34) enhances bone allograft integration in a clinically relevant pig model of segmental mandibulectomy. (25th June 2020) - Pelled, Gadi; Lieber, Raphael; Avalos, Pablo; Cohn‐Schwartz, Doron; Tawackoli, Wafa; Roth, Joseph; Knapp, Emma; Schwarz, Edward M.; Awad, Hani A.; Gazit, Dan; Gazit, Zulma
Abstract: Massive craniofacial bone loss poses a clinical challenge to maxillofacial surgeons. Structural bone allografts are readily available at tissue banks but are rarely used due to a high failure rate. Previous studies showed that intermittent administration of recombinant parathyroid hormone (rPTH) enhanced integration of allografts in a murine model of calvarial bone defect. To evaluate its translational potential, the hypothesis that rPTH would enhance healing of a mandibular allograft in a clinically relevant large animal model of mandibulectomy was tested. Porcine bone allografts were implanted into a 5‐cm‐long continuous mandible bone defect in six adult Yucatan minipigs, which were randomized to daily intramuscular injections of rPTH (1.75 μg/kg) and placebo ( n = 3). Blood tests were performed on Day 56 preoperation, Day 0 and on Day 56 postoperation. Eight weeks after the surgery, bone healing was analyzed using high‐resolution X‐ray imaging (Faxitron and micro computed tomography [CT]) and three‐point bending biomechanical testing. The results showed a significant 2.6‐fold rPTH‐induced increase in bone formation ( p = 0.02). Biomechanically, the yield failure properties of the healed mandibles were significantly higher in the rPTH group (yield load: p < 0.05; energy to yield: p < 0.01), and the post‐yield displacement and energy were higher in the placebo group ( p < 0.05), suggesting increased mineralized integration of the allograft in the rPTH group. In contrast to similar rPTH therapy studies in dogs, no signs of hypercalcemia, hyperphosphatemia, or inflammation were detected. Taken together, we provide initial evidence that rPTH treatment enhances mandibular allograft healing in a clinically relevant large animal model.